2017
DOI: 10.1177/2059436416688698
|View full text |Cite
|
Sign up to set email alerts
|

The bumpy road towards network convergence in China: The case of over-the-top streaming services

Abstract: The decoupling of content and distribution platform has changed television irrevocably. Potential opportunities promised by the integration of telecommunications, broadcast and Internet networks means television has become a strategic highland for relevant stakeholders including industry players and state regulators. In China, network convergence has been on the state agenda since the turn of the century, but has remained stubbornly hard to move forward. This article starts with a brief overview of the state p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…In authoritarian and illiberal regimes, internet-distributed television is already controlled and closely monitored by governments, alongside social media. 11 In liberal democracies, some services are already governed by policy in the sense that they benefit from public support, 12 and there are many proposals for interventions in the production and distribution of content and at the level of market competition. There is no reason to imagine that internet-distributed services cannot be licensed and regulated if governments wish to do so-with the proviso of course that informal services will persist alongside regulated media.…”
Section: Internet-distributed Television Can and Will Be Regulatedmentioning
confidence: 99%
“…In authoritarian and illiberal regimes, internet-distributed television is already controlled and closely monitored by governments, alongside social media. 11 In liberal democracies, some services are already governed by policy in the sense that they benefit from public support, 12 and there are many proposals for interventions in the production and distribution of content and at the level of market competition. There is no reason to imagine that internet-distributed services cannot be licensed and regulated if governments wish to do so-with the proviso of course that informal services will persist alongside regulated media.…”
Section: Internet-distributed Television Can and Will Be Regulatedmentioning
confidence: 99%
“…Yet, regardless of how we name such control mechanismssafe-content regulation or differential zoning-it is clear that China has moved steadfastly toward a selective commercialization and that its convergence with global digital capitalism is a stateengineered project (Bai, 2005;Y. Zhao, 2008;E. J. Zhao, 2017).…”
Section: Decree No 82-the Separation Of Station (Content) From Network (Pipelines)mentioning
confidence: 99%
“…Zhao (2017) studied the power negotiations between entrenched interest groups, Chinese bureaucracy, and social groups in the dynamics of market regulations related to telecommunications, broadcast, internet networks, and TV and observed that. .…”
Section: Is Creative Subversion a Tautology?mentioning
confidence: 99%